2016
DOI: 10.21548/29-2-1441
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Remediation and Subsequent Methanogenic Digestion of Sixteen Winery Wastewaters

Abstract: Sixteen winery wastewaters were partially characterised during peak wine production. Raw wastewaters were inoculated with Trametes pubescens MB 89 to establish whether a submerged culture could be used to treat winery wastewaters, and whether fungally-treated wastewater would be rendered more degradable by secondary biological treatment using methanogenic bacteria. Additionally, laccase activity was monitored during the treatment to determine if phenolic compounds present in the wastewater would stimulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Strong [35], in the treatment of wine distillery wastewater, reported that the fungally-treated samples all had much lower initial color absorbance values and the color increased in a number of the samples after anaerobic treatment of the fungally-pretreated. It is possible that some of the compounds that were depolymerized by the fungal treatment were repolymerized during the anaerobic treatment or possibly due to the increase in pH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong [35], in the treatment of wine distillery wastewater, reported that the fungally-treated samples all had much lower initial color absorbance values and the color increased in a number of the samples after anaerobic treatment of the fungally-pretreated. It is possible that some of the compounds that were depolymerized by the fungal treatment were repolymerized during the anaerobic treatment or possibly due to the increase in pH.…”
Section: Resultsmentioning
confidence: 99%
“…Strong [35] detected that the final removal efficiencies of phenol were generally better for anaerobic digestion than for the fungal treatment; however, these removal values were obtained within 2 weeks. In another study, the authors indicated that conversion of phenol and p-cresol is favorable under methanogenic conditions, but a lag phase of 30 days was observed [36].…”
Section: Resultsmentioning
confidence: 99%